Reduction of facial wrinkles by hydrolyzed water-soluble egg membrane associated with reduction of free radical stress and support of matrix production by dermal fibroblasts - Jensen GS; Shah B; Holtz R; Patel A; Lo DC (Dove Medical Press, 2016)
Gitte S Jensen,1 Bijal Shah,2 Robert Holtz,3 Ashok Patel,4 Donald C Lo2 1NIS Labs, Klamath Falls, OR, 2Department of Neurobiology, Center for Drug Discovery, Duke University Medical Center, Durham, NC, 3BioInnovation Laboratories, Inc., Lakewood, CO, 4Centre Manufacturing LLC, Eden Prairie, MN, USA Objective: The aim of this study was to evaluate the effects of water-soluble egg membrane (WSEM) on wrinkle reduction in a clinical pilot study and to elucidate specific mechanisms of action using primary human immune and dermal cell-based bioassays.Methods: To evaluate the effects of topical application of WSEM (8%) on human skin, an open-label 8-week study was performed involving 20 healthy females between the age of 45 years and 65 years. High-resolution photography and digital analysis were used to evaluate the wrinkle depth in the facial skin areas beside the eye (crow’s feet). WSEM was tested for total antioxidant capacity and effects on the formation of reactive oxygen species by human polymorphonuclear cells. Human keratinocytes (HaCaT cells) were used for quantitative polymerase chain reaction analysis of the antioxidant response element genes Nqo1, Gclm, Gclc, and Hmox1. Evaluation of effects on human primary dermal fibroblasts in vitro included cellular viability and production of the matrix components collagen and elastin.Results: Topical use of a WSEM-containing facial cream for 8 weeks resulted in a significant reduction of wrinkle depth (P<0.05). WSEM contained antioxidants and reduced the formation of reactive oxygen species by inflammatory cells in vitro. Despite lack of a quantifiable effect on Nrf2, WSEM induced the gene expression of downstream Nqo1, Gclm, Gclc, and Hmox1 in human keratinocytes. Human dermal fibroblasts treated with WSEM produced more collagen and elastin than untreated cells or cells treated with dbcAMP control. The increase in collagen production was statistically significant (P<0.05).Conclusion: The topical use of WSEM on facial skin significantly reduced the wrinkle depth. The underlying mechanisms of this effect may be related to protection from free radical damage at the cellular level and induction of several antioxidant response elements, combined with stimulation of human dermal fibroblasts to secrete high levels of matrix components. Keywords: anti-inflammatory, antioxidant response elements, collagen, elastin